Dampak Kelelahan Auditor Terhadap Perilaku Kewarganegaraan Organisasional: Pengujian Komitmen Professional Dan Kepusaan Kerja Sebagai Variabel Pemoderasi - Claudia Hana Debora; Andi Ina Yustina (JRAK: Journal of Accounting Research and Computerized Accounting, 2018)
Studies show that Organizational Citizenship Behavior (OCB) becomes an important part of an organization's sustainability, even to the individualistic level. But it is difficult to realize with this intention when workers experience high levels of work fatigue, because of excessive workload This study aims to investigate the impact of the Auditor Burnout or auditory fatigue in OCB aspect, which also investigates the dimensions that mediate between two aspects namely professional commitment and satisfaction of work simultaneously. This study uses primary data, where surveys are distributed to auditors working in public accounting firms that have international affiliations. The number of samples is 150 auditors. This study uses a survey to collect data and the data collected is then analyzed using SEM. The findings of this study indicate that auditor fatigue, mediated by professional commitment and job satisfaction, will have a negative impact on OCB. It can be concluded that auditors will experience fatigue or lack of application to OCB.